Soil respiration-driven CO2 pulses dominate Australia’s flux variability - Metz, Eva-Marie; Vardag, Sanam Noreen; Basu, Sourish; Jung, Martin; Ahrens, Bernhard; El-Madany, Tarek; Sitch, Stephen; Arora, Vivek K.; Briggs, Peter R.; Friedlingstein, Pierre; Goll, Daniel S.; Jain, Atul K.; et al. (Science, 2023)
The Australian continent contributes substantially to the year-to-year variability of the global terrestrial carbon dioxide (CO2) sink. However, the scarcity of in situ observations in remote areas prevents the deciphering of processes that force the CO2 flux variability. In this study, by examining atmospheric CO2 measurements from satellites in the period 2009-2018, we find recurrent end-of-dry-season CO2 pulses over the Australian continent. These pulses largely control the year-to-year variability of Australia’s CO2 balance. They cause two to three times larger seasonal variations compared with previous top-down inversions and bottom-up estimates. The pulses occur shortly after the onset of rainfall and are driven by enhanced soil respiration preceding photosynthetic uptake in Australia’s semiarid regions. The suggested continental-scale relevance of soil-rewetting processes has substantial implications for our understanding and modeling of global climate-carbon cycle feedbacks.
Im Titel ist die Zahl 2 tiefgestellt
Gesehen am 11.04.2023